PERENCANAAN GEOMETRIK JALAN BERBASIS BIM PADA JALAN PELABUHAN BANDAR SETIA RAJA - BERANCAH - Ihsan, Fikri Nugraha; Saputra, Hendra (Politeknik Negeri Bengkalis, 2023)
In line with the times, the world of construction is faced with various challenges, one of which is the demand for visualization both in project design and during post-implementation. Using digital data, BIM can identify project risks as well as actual physical conditions optimally. In addition, the implementation of BIM makes the design and construction process leaner and more transparent, improves accuracy in calculations, avoids mistakes during planning to implementation, and shortens execution time. In other words, BIM improves efficiency and accuracy through coordination between construction stakeholders. By utilizing BIM in the planning of Bandar Setia Raja-Berancah Port Road, Bengkalis District, Bengkalis Regency, Riau, BIM-based road geometric planning was carried out. The application of BIM is carried out in several stages, namely data collection, creating a geometric planning concept in Autodesk Infraworks, and then exporting it to Autocad Civil 3D to make detailed planning and calculation drawings. The conclusion obtained from this study is that BIM technology makes it very easy to make road geometric planning using Autodesk Infraworks and Autocad Civil 3D software, as well as to overcome the demands of project visualization.